HBM4EU chromates study: overall results and recommendations for the biomonitoring of occupational exposure to hexavalent chromium - Santonen, Tiina (2021)
Exposure to hexavalent chromium [Cr(VI)] may occur in several occupational activities, e.g., welding, Cr(VI) electroplating, and other surface treatment processes. The aim of this study was to provide EU-relevant data on occupational Cr(VI) exposure to support the regulatory risk assessment and decision-making. In addition, the capability and validity of different biomarkers for the assessment of Cr(VI) exposure were evaluated. The study involved nine European countries and involved 399 workers in different industry sectors with exposures to Cr(VI) such as welding, bath plating, applying or removing paint, and other tasks. We also studied 203 controls to establish a background in workers with no direct exposure to Cr(VI). We applied a cross-sectional study design and used chromium in urine as the primary biomonitoring method for Cr(VI) exposure. Additionally, we studied the use of red blood cells (RBC) and exhaled breath condensate (EBC) for biomonitoring of exposure to Cr(VI). Personal measurements were used to study exposure to inhalable and respirable Cr(VI) by personal air sampling. Dermal exposure was studied by taking hand wipe samples. The highest internal exposures were observed in the use of Cr(VI) in electrolytic bath plating. In stainless steel welding, the internal Cr exposure was clearly lower when compared to plating activities. We observed a high correlation between chromium urinary levels and air Cr(VI) or dermal total Cr exposure. Urinary chromium showed its value as a first approach for the assessment of total, internal exposure. Correlations between urinary chromium and Cr(VI) in EBC and Cr in RBC were low, probably due to differences in kinetics and indicating that these biomonitoring approaches may not be interchangeable but rather complementary. This study showed that occupational biomonitoring studies can be conducted successfully by multi-national collaboration and provide relevant information to support policy actions aiming to reduce occupational exposure to chemicals.